Glomus Tumor of Sella Turcica With Synaptophysin Expression Mimicking Pituitary Adenoma. (June 2020) - Tsang, Jason C. H.; Ng, C. S.; Fung, C. F.; Chan, John K. C.; Cheuk, Wah
Glomus tumor can rarely arise in the central nervous system as a sella turcica mass. In this article, we report a case of sellar glomus tumor in a female patient who presented at the age of 8 years with visual impairment. The tumor recurred at 4 years and 26 years after initial excision and gamma knife therapy. Histologic examination showed a monotonous population of oval cells accompanied by delicate blood vessels, features mimicking pituitary adenoma. The tumor showed histologic progression at the second recurrence. Synaptophysin staining was positive, but chromogranin and CD56 were negative. The tumor cells were negative for epithelial markers but expressed actin and SMA. Awareness of the rare occurrence of glomus tumor at this region, careful analysis of morphology, and appropriate immunohistochemical workup are essential to solve this diagnostic challenge. The clinicopathologic features of all previously reported cases are reviewed.